INTRA-SPECIFIC POLYMORPHISM OF SOCIAL INSECT CASTES (REMUNOM, 2026)
Polymorphism encompasses all discontinuities occurring within the same phase of the life cycle. The probable evolutionary sequence of polymorphism involved an initial differentiation, starting from the queen, along a size gradient, followed by the segregation of two distinct size groups and the elimination of intermediate sizes. Social bees have a female population divided into two castes (workers and queens) that are very different from each other, both morphologically and physiologically. Female ants are divided into three castes: workers, soldiers, and queens. Males, on the other hand, are not divided into castes, but in a more abstract sense, they can be considered a fourth caste. Differentiation patterns in social wasps are quite variable; there may be no dimorphism among females, with differences being only physiological and behavioral. Polymorphism is richest in Isoptera; juvenile stages are useful, their growth can be arrested or regressed, and both sexes are frequently socialized with function differentiation. The intra-specific polymorphism of social insect castes is responsible for a large part of the evolutionary success of this group.